2021
DOI: 10.1111/1365-2745.13732
|View full text |Cite
|
Sign up to set email alerts
|

Contribution of microbial photosynthesis to peatland carbon uptake along a latitudinal gradient

Abstract: 1. Phototrophic microbes, also known as micro-algae, display a high abundance in many terrestrial surface soils. They contribute to atmospheric carbon dioxide fluxes through their photosynthesis, and thus regulate climate similar to plants.However, microbial photosynthesis remains overlooked in most terrestrial ecosystems. Here, we hypothesise that phototrophic microbes significantly contribute to peatland C uptake, unless environmental conditions limit their development and their photosynthetic activity.2. To… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
42
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 20 publications
(48 citation statements)
references
References 134 publications
(157 reference statements)
5
42
1
Order By: Relevance
“…The positive correlation between soil algal NPP and increasing vegetation cover might be seen as counterintuitive given that plant canopy reduces the light availability at the soil surface. However, most microscopic algae show optimal photosynthesis at low light intensity (Ritchie & Larkum, 2012; Hamard et al ., 2021a) by optimizing light harvesting at low light flux (Perrine et al ., 2012). Given the positive relationship between total microbial abundance and metabolic rates in soils (Johnston & Sibly, 2018), our results further presume a simultaneous increase in soil algal abundance and productivity with increasing environmental favorability, which corroborates previous findings in aquatic systems (Y. Liang et al ., 2017).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The positive correlation between soil algal NPP and increasing vegetation cover might be seen as counterintuitive given that plant canopy reduces the light availability at the soil surface. However, most microscopic algae show optimal photosynthesis at low light intensity (Ritchie & Larkum, 2012; Hamard et al ., 2021a) by optimizing light harvesting at low light flux (Perrine et al ., 2012). Given the positive relationship between total microbial abundance and metabolic rates in soils (Johnston & Sibly, 2018), our results further presume a simultaneous increase in soil algal abundance and productivity with increasing environmental favorability, which corroborates previous findings in aquatic systems (Y. Liang et al ., 2017).…”
Section: Resultsmentioning
confidence: 99%
“…Despite their apparent global distribution, our understanding of the ecological preferences of soil algae across broad spatial scales remains limited. Though some previous work has suggested that soil moisture availability is a key driver of soil algal net primary productivity (NPP) (Brostoff et al, 2005;Yoshitake et al, 2010;Hamard et al, 2021a,b), other studies have highlighted the importance of temperature (Shimmel & Darley, 1985;Dettweiler-Robinson et al, 2018) or plant community composition (Hamard et al, 2021a), and it remains unclear how predictable soil algal NPP is at larger spatial scales. As a result, quantitative information on soil algal C fixation remains mostly restricted to drylands (Rodriguez-Caballero et al, 2018) and is not readily available at the global scale.…”
Section: Introductionmentioning
confidence: 99%
“…In total, we identified 129 phototrophic OTUs distributed in nine phyla. This richness is lower than the one found in peatland lawns along a 3000 km latitudinal gradient (351 OTUs and 11 phyla with 16S/18S metabarcoding; Hamard et al ., 2021) or than the one found in a peatland along a gradient of drainage (794 OTUs with 18S metabarcoding; Heger et al ., 2018). The 23S metabarcoding analyses should perform better than the 18S or 16S analyses to reveal the presence of phototrophic OTUs (Marcelino and Verbruggen, 2016).…”
Section: Discussionmentioning
confidence: 90%
“…organisms combining photoautotrophy and heterotrophy such as some Ciliophora, Lobosa, many Alphaproteobacteria or Cyanobacteria), or photoheterotrophs species (e.g. Chloroflexia) (Jassey et al ., 2015; Nowicka and Kruk, 2016; Hamard et al ., 2021). Only a handful studies suggest that phototrophic microbes fix significant amounts of atmospheric C in northern peatlands (Goldsborough and Robinson, 1996; Gilbert et al ., 1998b; Wyatt et al ., 2012; Jassey et al ., 2015; Hamard et al ., 2021).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation